The Cash Dividend : The Rise of Cash Transfer Programs in Sub-Saharan Africa - Garcia, Marito; Moore, Charity M. T. (World Bank, 2012)
The results of the review do not disappoint. The authors identified more than 120 cash transfer programs that were implemented between 2000 and mid-2009 in Sub-Saharan Africa. These programs have varying objectives, targeting, scale, conditions, technologies, and more. A sizable number of these programs conducted robust impact evaluations that provide important information, presented here, on the merits of cash transfer programs and their specific design features in the African context. The authors present summary information on programs, often in useful graphs, and provide detailed reference material in the appendixes. They highlight how many of the cash transfer programs in Africa that had not yet begun implementation at the time of writing will continue to provide important evaluation results that will guide the design of cash transfer programs in the region. In addition to presenting data and analysis on the mechanics of the programs, the authors discuss issues related to political economy. They highlight the importance of addressing key tradeoffs in cash transfers, political will, and buy-in, and they emphasize the need to build evidence-based debates on cash transfer programs. Useful anecdotes and discussion illustrate how some programs have dealt with these issues with varying degrees of success. This text will serve as a useful reference for years to come for those interested in large- and small-scale issues of cash transfer implementation, both in Africa and beyond. However, the book is not an end in itself. It also raises important questions that must be addressed and knowledge gaps that must be filled. Therefore, it is useful both in the information it provides and in the issues and questions it raises.